(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Most linguists suggest that all languages have some universal principles, even though a significant number of languages worldwide appear to have nothing in common at first glance. These guidelines comprise an established body of rules known as a Universal Grammar. It is true that the way sentences are formed in Hungarian, an agglutinative language, and Farsi, a fusional language that is modern Persian, appears to have very little, if anything, in common. It’s also true that Italian verbs have six conjugations, while Chinese verbs have none (they are inflected for number, tense, etc.). Nonetheless, it is evident that all four of these languages use verbs and follow a similar pattern of sentence construction.